Obtaining an electronic circuit based in III-V semiconductor application around the frequency of 20 MHz (Revista de Investigaciones Universidad del Quindío, 2012)
In this work, obtaining an electronic circuit configuration based on GaSb, for an application filter tuned about 20 MHz was implemented and automated technique of amplitude and phase spectroscopy to study metal-semiconductor-metal systems, at a measuring frequency range comprised from 0.15 MHz to 60 MHz and a voltage amplitude range comprised from 0 mV to 500 mV. Was the study of amplitude and phase diagrams in samples of GaSb and GaSb / GaSb, being a narrow resonance peak around 23 MHz, which was modeled theoretically by an equivalent electrical circuit tuned filters based. From this electrical behavior was designed and implemented an application of the filter circuit, with a response frequency tuned around 20 MHz
Keywords: Amplificador; espectroscopia eléctrica; filtros sintonizados; semiconductores III-V